Analisis Daya Saing Universitas di Purworejo dengan Pendekatan Five Forces Porter - Hubi Rahmat Andika; Ishak, Ishak (MAMEN: Jurnal Manajemen, 2025)
This study analyzes the competitive position of universities in Purworejo, focusing on Universitas Muhammadiyah Purworejo (UMPWR), using Porter’s Five Forces framework. The increasingly intense competition in the higher education sector—driven by digital disruption and changing student preferences—demands that universities formulate effective strategies to remain competitive. Using a descriptive qualitative approach and a case study method, this research evaluates the five competitive forces: the threat of new entrants, the bargaining power of suppliers, the bargaining power of buyers, the threat of substitute products, and the intensity of rivalry among existing competitors. Data were collected through document analysis and literature review using secondary sources from PDDikti, BAN-PT, and official university data. The findings indicate that UMPWR faces threats from digital-based universities such as MOOCs and online campuses, but it holds strengths in operational scale, local market leadership, Islamic identity, and alumni networks. The study concludes that strengthening digital infrastructure, diversifying academic programs, and leveraging institutional identity are key strategies to enhance competitiveness. This research contributes to the practical discourse on strategic planning for private universities in Indonesia.